Comparison of methylxantines, trigonelline, nicotinic acid and nicotinamide contents in brews of green and processed Arabica and Robusta coffee beans – Influence of steaming, decaffeination and roasting processes on coffee beans. (May 2020) - Jeszka-Skowron, Magdalena; Frankowski, Robert; Zgoła-Grześkowiak, Agnieszka
Abstract: The differences among several popular brewed beverages in relation to content of caffeine, theobromine, theophylline, trigonelline, nicotinic acid and amide were studied. Caffeine, the main active component of the green and roasted Arabica and Robusta coffees, was also found in Yerba mate tea and other beverages such as teas. On the other hand, it has been found that roasted grain beverages that are used as a coffee substitute contain 5000-10000 times less caffeine. In addition the effect of coffee treatment such as roasting, steaming and decaffeination processes of coffee beans was analyzed. It was shown that the steaming and/or light roasting processes have influenced the methylxantines and trigonelline content. Decaffeination process has decreased the level of theobromine and theophylline and increased the content of nicotinic acid and there was no change in nicotinamide in Vietnam Robusta coffees. Highlights: Methylxantines, trigonelline, nicotinic acid and amide were determined by LC-MS/MS. Green and roasted coffees, Yerba mate, and roasted grain beverages were studied. Steaming and decaffeination as well as roasted processes were analyzed.